Layla - Hoover, Colleen (USA : Montlake - a trademark of Amazon Inc., 2023)
"When Leeds meets Layla, he's convinced he'll spend the rest of his life with her--until an unexpected attack leaves Layla fighting for her life. After weeks in the hospital, Layla recovers physically, but the emotional and mental scarring has altered the woman Leeds fell in love with. In order to put their relationship back on track, Leeds whisks Layla away to the bed-and-breakfast where they first met. Once they arrive, Layla's behavior takes a bizarre turn. And that's just one of many inexplicable occurrences"--Provided by publisher.
Keywords: Man-woman relationships -- Fiction; Assault and battery -- Fiction; Triangles (Interpersonal relations) -- Fiction; Psychic ability -- Fiction; FICTION / Romance / Suspense; FICTION / Women; FICTION / Thrillers / Supernatural; Assault and battery; Man-woman relationships; Psychic ability; Triangles (Interpersonal relations); Love triangles; Sexual relationships; Man-woman relationship -- Fiction; Interpersonal relations -- Fiction; Parapsychology -- Fiction; Paranormal fiction; Romance fiction; Suspense fiction; Love stories; Thrillers (Fiction); Fiction; Paranormal fiction; Romance fiction; Romantic suspense fiction; Paranormal fiction; Romance fiction; Thrillers (Fiction); Novels